New Sensitive One-Step Real-Time Duplex PCR Method for Group A and B HIV-2 RNA Load - Avettand-Fenoel, Véronique (American Society for Microbiology, 2014)
The Agence Nationale de Recherche sur le Sida et les hépatites virales (ANRS) previously developed a widely used method for HIV-1 RNA quantification (Biocentric). Here, we report the development of a new specific and sensitive method for HIV-2 RNA quantification, based on an adaptation of the existing HIV-1 protocol. The new test is based on TaqMan one-step reverse transcription-quantitative PCR (qRT-PCR) targeting two conserved consensus regions of HIV-2 (long terminal repeat [LTR] and gag). Analytic performances were determined in three laboratories. Clinical performances were evaluated on 100 plasma samples from HIV-2-infected patients (groups A, B, and H) by comparison with the assay currently used for the ANRS HIV-2 cohort. The specificity was 100%. Sensitivity was 50 copies/ml (cp/ml) and was optimized to 10 cp/ml. The within-run coefficients of variation in the three laboratories varied from 0.54% to 1.61% at 4 log(10) copies/ml and from 7.24% to 14.32% at 2 log(10) cp/ml. The between-run coefficients of variation varied from 2.28% to 6.43%. Of the 39 clinical samples below 2 log(10) in the current assay, the new test improved the detection or quantification of 17 samples, including eight group B samples. For quantifiable samples, similar loads were obtained with the two assays for group A samples. The median difference between the two assays for group B samples was +0.18 but with greater heterogeneity than for group A. The HIV-2 group H sample had similar results with the two assays. This new assay is highly sensitive and accurately quantifies the most prevalent HIV-2 groups. This test will be useful for monitoring low viral loads in HIV-2-infected patients.